MATERIALS AND METHODS FOR INCREASING GOLD RECOVERY FROM LEACHATE SOLUTIONS - KNESEL, Gabriela (2024)
The subject invention provides safe, environmentally-friendly compositions and efficient methods for extracting impurities from gold ore. More specifically, the subject invention provides compositions derived from microorganisms for pre-leaching treatments of gold ore, which can be used for reducing carbonaceous material in gold ore.